Intrathoracic Gastric Volvulus presenting with GIT Bleed - Kadam, Rahul; Prasad, VSV (Journal of Neonatal Surgery, 2017)
Intrathoracic gastric volvulus in neonatal period is a life-threatening surgical emergency. We report a case of neonate with respiratory distress and GI bleeding who was diagnosed to have congenital diaphragmatic eventration with Intrathoracic gastric volvulus.